Influence of Popular Culture on Adolescent Personality in Indonesia: A Mixed-Methods Study - Bamantara Arzaquna (Institute of Computer Science (IOCS), 2024)
This research investigates the influence of popular culture on the personality of adolescents in Indonesia through a mixed-methods approach. Drawing on theories of cultural hybridity, media literacy, and social comparison, the study examines how media consumption habits, cultural influences, and individual characteristics intersect to shape adolescent development within the Indonesian context. Qualitative data from in-depth interviews and focus group discussions reveal the diverse experiences and perspectives of Indonesian adolescents in navigating popular culture influences on their identity negotiation, media literacy, and social comparison processes. Quantitative analyses of survey data provide insights into the prevalence and patterns of popular culture consumption among Indonesian adolescents, as well as its associations with personality traits and psychosocial well-being. The findings highlight the complex interplay between globalized media influences and Indonesian cultural values in shaping adolescent personality, underscoring the importance of promoting critical media literacy skills, resilience-building strategies, and inclusive representations. While this research contributes valuable insights into the influence of popular culture on adolescent development in Indonesia, limitations and directions for future research are also discussed. Overall, this study offers implications for theory, practice, and policy in promoting positive youth outcomes amidst the complexities of contemporary media environments.